Near-infrared fluorescence as a method for determining single-wall carbon nanotube extraction conditions in aqueous two polymer phase extraction. (15th September 2020) - Sims, Christopher M.; Fagan, Jeffrey A.
Abstract: Near-infrared fluorescence emission from single-wall carbon nanotubes (SWCNTs) is demonstrated as a measurement technique enabling the determination of aqueous surfactant concentration conditions yielding upper or lower polymer phase extraction in aqueous two-polymer phase extraction (ATPE) separations. From measurements on single-phase dispersions of multiple SWCNT specie mixtures, the fluorescence intensity of a given SWCNT (n, m) species is demonstrated to correlate directly to partitioning in an ATPE separation, as determined by the type of surfactant molecule comprising a preponderance of the adsorbed interfacial layer on that species. This methodology enables rapid quantitative determination of partitioning conditions for individual (n, m) species of SWCNTs without ambiguity of mass transfer limitations or interfacial adsorption present when conducting the ATPE separation itself, while also allowing for ready investigation of complicating factors such as temperature effects or SWCNT enantiomers. Graphical abstract: An aqueous two-polymer phase extraction experiment at appropriate surfactant concentrations intermediate to quantified partition coefficient curves results in macroscopic separation of single-wall nanotube species. Image 1